The Correlation Between the Waitress's Attitude to HIV/AIDS and Their Anxiety Related to Contracting HIV/AIDS - Ni Made Dwi Yunica Astriani; I Dewa Ayu Rismayanti; I Made Sundayana; Putu Indah Sintya Dewi (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2017)
Introduction: Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system and weakens the body’s ability to resist disease. People thus become susceptible to various infections. This study aims to investigate the correlation between the waitress’s attitude to HIV/AIDS and their anxiety focused on contracting HIV/AIDS in Dahlia and Sahara Bar and Karaoke. Methods: This research was non-experimental, and utilized a cross-sectional approach. Collecting the data used the researcher’s understanding of HIV/AIDS test and consisted of 20 items. The study used the Zung Self Rating Anxiety Scale comprised of 20 elements. The subjects of this study was 30 people. The subjects of this study were women who worked in nightclubs as waitresses in two bars and karaoke in 2017. Results: Data was analyzed using the Spearman’s rho test. The results showed that the correlation coefficient = -0.761 with p= 0.000 (p<0.05). This means that H0 rejected and Ha accepted. Conclusions: Based on the data analysis, it can be concluded that there is a correlation between the waitress’s Attitude to HIV/AIDS and their anxiety over the potential risk of contracting HIV/AIDS in Dahlia and Sahara Bar and Karaoke. Based on the results of the study, it is suggested that information about HIV/AIDS should be provided through health education and HIV prevention resources.